DEVELOPMENT OF THE PRINCIPLES AND PRACTICE OF HUMAN FACTOR - Madaliev, A.A. (International Journal of Psychosocial Rehabilitation, 2020)
Activation of the human factor is increasingly important in light of the increasing personal role of the employee based on the concept of management. However, this is not to say that this issue is still fully resolved and is being applied in practice. There are many aspects that need to be studied in the scientific sense, and its constant activation is of great importance in the socio-economic life.